Knowledge and practice of health care workers towards post exposure prophylaxis in the era of low and stable HIV prevalence in Southwestern Nigeria - Wasiu Olalekan Adebimpe (Faculty of Pharmacy, Cairo University, 2018)
Nigeria ranks top among the countries with the highest burden of Human Immune-deficiency Virus (HIV) infection. Despite ready-made access to HIV care, Post-Exposure Prophylaxis (PEP) practices have not increased commensurately due to several gaps within the health sector. This research was undertaken to assess knowledge and practice of health care workers towards PEP of HIV in Southwestern Nigeria. A descriptive cross sectional study was carried out among 300 health care workers selected using the multi-staged sampling method. Research instruments used were self-administered pre tested and semi structured questionnaires. Data collected were analyzed using the SPSS software version 17.0. One hundred and four (34.7%) of respondents said they occasionally recap used needles, one hundred and eighty-one (60.3%) have heard about PEP. Only 2.7% had good mean knowledge scores while 57.3% and 40.0% had moderate and poor mean knowledge scores of PEP respectively. Only 24 (13.3%) knew the correct number of drugs combinations, 36 (19.9%) knew the antiretroviral drugs administered; 113 (62.4%) believed that the drugs were antibiotics. Forty-four (14.7%) had needle stick injuries in the last 6 months, out of which 29 (65.9%) used PEP. Predictors of good knowledge of PEP on logistic regression include male gender, having spent more than 5 years in hospital practice, having heard about PEP and being aware of the national PEP guidelines. There is a need to create better awareness about PEP among health care workers to reduce and prevent occupational HIV transmission.